Cast-in-place fasteners under tensile loading: A critical review. (July 2022) - Di Nunzio, G.; Muciaccia, G.
Abstract: The correct detailing of discontinuity regions (D-regions), particularly of fastenings to concrete, is becoming a crucial task in modern structural engineering. In the past, a lot of efforts have been dedicated to study metal fasteners in concrete thus resulting in various mechanical descriptions of their structural behaviour. On this basis, semi-empirical models were proposed in which geometrical and mechanical parameters were individually evaluated. However, looking at all the factors in a larger picture, potential critical issues arise, particularly regarding cast-in-place fasteners. This paper presents a critical review on those aspects which may strongly influence the response under tensile loading. The influence of bearing pressure, the presence of reinforcement, as well as the interaction with the concrete member and in groups, are presented and commented.